A Uniform-Gaussian distributed heat source model for analysis of residual stress field of S355 steel T welding. (December 2018) - Li, Tianci; Zhang, Lele; Chang, Chao; Wei, Liang
Highlights: A combined heat source model is proposed for mechanical simulation of residual stress in a T type welding joint. The model is applicable to simulate welding cases when electric arc is moving across an angled structure. The numerical results coincide well with results measured by X-ray diffraction and hole drilling methods. The largest width of the residual stress region reached the value of around 18 mm for S355 steel T-joint with a welding method of MIG. Abstract: A novel combined heat source model is derived for the simulation of the residual stress field of a T welding. The model is derived combining Gaussian surface and uniform volume heat source, and is applicable to simulate welding process as the electric arc is moving across an angled structure. By both physical characteristics of T and arc welding process, one part of heat input is from the welding arc acting in the workpiece surface, the other is from the molten metal droplets. The two portions are accurately calculated by Gaussian surface heat source distribution and uniform volume source. The numerical simulation of the welding process for a S355 steel T welding based on this novel model has been done and obtain the transient temperature field, stress evolution and residual stress field of the structure. The comparison between measured results by the hole drilling and X-ray diffraction (XRD) and simulation indicates that the combined heat source is sufficient to allow for an overall prediction of the entire welding process of T joints.